Giardiasis in Protein Calorie Malnutrition at Gadjah Mada Hospital, Y ogyakarta - Soehadi Soehadi; Soeprapto Soeprapto; Moenginah P. A.; Ismangoen Ismangoen; Noerhayati S.; Siti Musfiroh (Paediatrica Indonesiana, 1980)
The study consisted of forty-one patients hospitalized at the Child Health Department of the Gadjah Mada Hospital in Yogyakarta: 24 children were suffering from PCM with a body weight of more than 60% of the Harvard standard and 17 children from PCM with a body weight of less than 60% of the Harvard standard. The stools of these patients were examined for Giardia lamblia. The result was I6 (39.02%) positive. The Lipiodol Absorption Test of the patients with Giardia lamblia revealed : 40% from the PCM with a body weight of more than 60% of the Harvard standard were negative. 8I.82% from the PCM with a body weight of less than 60% of the Harvard standard were negative. The lower the nutritional status the higher the risk for Giardia infection.